THE POTENTIAL OF NYAMPLUNG LEAF EXTACT AS A NATURAL ANTICOAGULANT - Widia Rahmatullah (Politeknik Kesehatan Bhakti Setya Indonesia, 2021)
Anti-coagulants are blood clotting inhibitors by inhibiting the factors that can cause blood clotting. Anticoagulants are very useful in the field of hematology by adding anticoagulants to the blood to keep the speciment preserved without affecting the morphology of blood cells, platelet counts, hemoglobin check, leukocyte count and blood group determination. EDTA is anticoagulant that is often used in blood tests. The use of chemical anticoagulants is very expensive. Research is needed to find cheaper alternatives anticoagulants. One of the mangrove plants that can be used as antocoagulant is nyamplung (Calophyllum inophylum). This research was conducted using a completely randomized design with three treatments, each with 10 repetitions. Observations were made on hour later after the sample was givent teh following treatments: tube 1: control blood (untreated). Tube 2: blood + leaf extract Callophyllum inophyllum, tube 3 : blood + EDTA. Parameters for visual observation of blood samples, observation of blood clotting activity, counting the number of platelets and erythrocytes. The results showed that the number of platelets in blood treatments was added with Callophyllum inophyllum leaf exstract with an average of 1.759.000 cells/mm3. Indicating the presence of anticoagulant properties in this plant. The result also showed that EDTA was more effective at inhibiting blood clotting compared to Callophyllum inophyllum leaft exstract.